How Authoritarian Leadership Affects Employee's Helping Behavior? The Mediating Role of Rumination and Moderating Role of Psychological Ownership - Asim, Muhammad; Zhiying, Liu; Nadeem, Muhammad Athar; Ghani, Usman; Arshad, Mahwish; Yi, Xu (Frontiers in Psychology, 2021)
Interpersonal helping behaviors, i.e., voluntarily assisting colleagues for their workplace related problems, have received immense amount of scholarly attention due to their significant impact on organizational effectiveness. However, scarce research is found to explore the inhibiting factors that may hinder these behaviors. Building on conservation of resources theory, this study investigates the adverse impacts of authoritarian leadership on helping behaviors among employees. Moreover, psychological ownership plays a significant moderating role, and rumination has a mediating effect on the relationship between authoritarian leadership and helping behaviors. The investigation of 264 samples reveals that authoritarian leadership has adverse impacts on helping behavior. Further, rumination also mediates the relationship between authoritarian leadership and employees’ helping behaviors. The findings also show that psychological ownership moderates the positive relationship between rumination and authoritarian leadership. Besides, this study brings evidence of authoritarian leadership and its impacts from a high-power distance-oriented country i.e., Pakistan.